Ensuring Funding for Victim Support Services - Ivankovic, Aleksandra (World Bank, Washington, DC, 2017)
The World Bank and the Multi Donor Trust Fund for Justice Sector Support (MDTF-JSS), in partnership with Victim Support Europe (VSE), are implementing a number of activities aimed at strengthening victim support services in Serbia. This report examines funding of victim support services in France, Finland and UK and outlines the various policy options available to Serbia.